2012
DOI: 10.3109/00016489.2012.699196
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hearing outcome using a Nitinol versus Teflon prosthesis in stapedotomy

Abstract: There was no significant difference between the two groups in the postoperative air-bone gap and air-bone gap closure at 1, 2, 3, and 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 8 publications
0
23
1
Order By: Relevance
“…; date of last search was April 6, 2015). We included 22 articles after selection based on title and abstract and subsequent full text screening . No articles were excluded based on language, nor were any articles excluded because we could not retrieve the full‐text version.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…; date of last search was April 6, 2015). We included 22 articles after selection based on title and abstract and subsequent full text screening . No articles were excluded based on language, nor were any articles excluded because we could not retrieve the full‐text version.…”
Section: Resultsmentioning
confidence: 99%
“…This study also reported statistically significant results. In two studies that reported statistically significant results and in four studies without statistically significant results, it was not clear how postoperative air‐bone gaps were calculated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations